Biological Control Potential of Penicillium brasilianum against Fire Blight Disease - Kim, Yeong Seok; Ngo, Men Thi; Kim, Bomin; Han, Jae Woo; Song, Jaekyeong; Park, Myung Soo; Choi, Gyung Ja; Kim, Hun (The plant pathology journal, 2022)
Erwinia amylovora is a causative pathogen of fire blight disease, affecting apple, pear, and other rosaceous plants. Currently, management of fire blight relies on cultural and chemical practices, whereas it has been known that few biological resources exhibit disease control efficacy against the fire blight. In the current study, we found that an SFC20201208-M01 fungal isolate exhibits antibacterial activity against E. amylovora TS3128, and the isolate was identified as a Penicillium brasilianum based on the β-tubulin (BenA) gene sequence. To identify active compounds from the P. brasilianum culture, the culture filtrate was partitioned with ethyl acetate and n-butanol sequentially. From the ethyl acetate layer, we identified two new compounds (compounds 3-4) and two known compounds (compounds 1-2) based on spectroscopic analyses and comparison with literature data. Of these active compounds, penicillic acid (1) exhibited promising antibacterial activity against E. amylovora TS3128 with a minimal inhibitory concentration value of 25 μg/ml. When culture filtrate and penicillic acid (125 μg/ml) were applied onto Chinese pearleaf crab apple seedlings prior to inoculation of E. amylovora TS3128, the development of fire blight disease was effectively suppressed in the treated plants. Our results provide new insight into the biocontrol potential of P. brasilianum SFC20201208-M01 with an active ingredient to control fire blight.